2018
DOI: 10.1002/brb3.1067
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide on background eeg activity in brain tumor‐related epilepsy patients: A case series study

Abstract: ObjectiveTherapeutic doses of antiepileptic drugs (AEDs) may alter EEG background activity, which is considered an index of the functional state of the brain. Quantitative analysis (qEEG) of EEG background activity is a valid instrument to assess the effects of many centrally active drugs on the central nervous system, including AEDs. Lacosamide (LCM) is a new AED that could be a valid therapeutic choice in patients with brain tumor‐related epilepsy (BTRE).MethodsWe used qEEG to analyze the possible effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…With regard to IED, we could further consider support for this biomarker as a predictor of treatment failure, coming from different types of evidence, such as four studies 30,88–90 that classified an EEG as abnormal defined only by the presence of IED, three studies 63,81,91 investigating the presence of IED, and particularly six studies 53,54,62,78,79,92 investigating different statistics of IED counts in different types of ASMs. However, not all ASMs have been investigated, and interpretability of results was also reduced by 42 studies that investigated initiation of adjunct ASM to mono‐ or polytherapy, particularly 20 underpowered studies 44,50,55,57,60,62,69,71–73,80,87,88,92–98 investigating polytherapy combinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to IED, we could further consider support for this biomarker as a predictor of treatment failure, coming from different types of evidence, such as four studies 30,88–90 that classified an EEG as abnormal defined only by the presence of IED, three studies 63,81,91 investigating the presence of IED, and particularly six studies 53,54,62,78,79,92 investigating different statistics of IED counts in different types of ASMs. However, not all ASMs have been investigated, and interpretability of results was also reduced by 42 studies that investigated initiation of adjunct ASM to mono‐ or polytherapy, particularly 20 underpowered studies 44,50,55,57,60,62,69,71–73,80,87,88,92–98 investigating polytherapy combinations.…”
Section: Resultsmentioning
confidence: 99%
“…three studies 63,81,91 investigating the presence of IED, and particularly six studies 53,54,62,78,79,92 investigating different statistics of IED counts in different types of ASMs. However, not all ASMs have been investigated, and interpretability of results was also reduced by 42 studies that investigated initiation of adjunct ASM to mono-or polytherapy, particularly 20 underpowered studies 44,50,55,57,60,62,69,[71][72][73]80,87,88,[92][93][94][95][96][97][98] investigating polytherapy combinations.…”
Section: Context Search Resultsmentioning
confidence: 99%
“…[25][26][27][28][29] Less data are present in literature about the third-generation ASMs, with few reports about lacosamide (LCM) or eslicarbazepine (ESL). [30][31][32] Cognitive consequences of ASMs are frequent in both adults and children, since treatment with ASMs, although controlling seizure, can impair learning abilities, cause sleepiness, and reduce the processing speed and brain capacities due to sedation and depression of brain activity. In keeping with this evidence, several ASMs (in particular, first-generation ASMs-phenytoin, carbamazepine, phenobarbitol) reduce fast EEG rhythms by increasing theta activity and reducing alfa and beta qEEG rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…25-29 Less data are present in literature about the third-generation ASMs, with few reports about lacosamide (LCM) or eslicarbazepine (ESL). 30-32…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that LEV and LCM have fewer side effects than conventional ASDs. [5,6,13,14] A previous systematic review that investigated the e cacy of LEV for BTRE, including 21 articles (3 randomized controlled trials, 7 prospective observational studies, and 11 retrospective observational studies), did not examine the incidence of ASD-related eruptions.…”
Section: Levetiracetam-and Lacosamide-associated Skin Rashmentioning
confidence: 99%